2017
DOI: 10.1007/s00338-017-1585-6
|View full text |Cite
|
Sign up to set email alerts
|

Globally intertwined evolutionary history of giant barrel sponges

Abstract: Three species of giant barrel sponge are currently recognized in two distinct geographic regions, the tropical Atlantic and the Indo-Pacific. In this study, we used molecular techniques to study populations of giant barrel sponges across the globe and assessed whether the genetic structure of these populations agreed with current taxonomic consensus or, in contrast, whether there was evidence of cryptic species. Using molecular data, we assessed whether giant barrel sponges in each oceanic realm represented se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 73 publications
1
27
0
Order By: Relevance
“…The species investigated were the known LMA sponges: Jaspis splendens ( Js ) (order Tetractinellida), Stylissa carteri ( Sc ) , and Stylissa massa ( Sm ) (order Scopalinida), and the known HMA sponges: Hyrtios erectus ( He ) (family Thorectidae, order Dictyoceratida) and Xestospongia testudinaria ( Xt ) (family Petrosiidae, order Haplosclerida). All of these species are widespread species and have been observed from the Western Indian Ocean to the Pacific Ocean (Cleary et al, ; Coelho et al, ; Swierts et al, ). In addition, four species were investigated of which the HMA/LMA status was unknown: Ectyoplasia coccinea ( Ec ) (family Raspailiidae, order Axinellida), Liosina paradoxa ( Lp ) (family Dictyonellidae, order Bubarida), Paratetilla bacca ( Pb ) (family Tetillidae, order Tetractinellida), and Petrosia aff.…”
Section: Methodsmentioning
confidence: 99%
“…The species investigated were the known LMA sponges: Jaspis splendens ( Js ) (order Tetractinellida), Stylissa carteri ( Sc ) , and Stylissa massa ( Sm ) (order Scopalinida), and the known HMA sponges: Hyrtios erectus ( He ) (family Thorectidae, order Dictyoceratida) and Xestospongia testudinaria ( Xt ) (family Petrosiidae, order Haplosclerida). All of these species are widespread species and have been observed from the Western Indian Ocean to the Pacific Ocean (Cleary et al, ; Coelho et al, ; Swierts et al, ). In addition, four species were investigated of which the HMA/LMA status was unknown: Ectyoplasia coccinea ( Ec ) (family Raspailiidae, order Axinellida), Liosina paradoxa ( Lp ) (family Dictyonellidae, order Bubarida), Paratetilla bacca ( Pb ) (family Tetillidae, order Tetractinellida), and Petrosia aff.…”
Section: Methodsmentioning
confidence: 99%
“…Giant barrel sponges are a particularly suitable model for such research since they have a broad distribution on coral reefs around the globe and have an intricate phylogeny (Swierts et al . 2013 , 2017 ). While three giant barrel sponge species have been described so far, namely Xestospongia muta from the Caribbean, Xestospongia testudinaria from the Indo-Pacific and Xestospongia bergquistia from the northeastern coast of Australia, molecular studies comparing these giant barrel sponge species were unable to find a separation that correlated with the species descriptions as they exist today (Setiawan et al .…”
Section: Introductionmentioning
confidence: 99%
“… 2016a , Swierts et al . 2017 ). Recent studies have, furthermore, revealed that giant barrel sponges around the globe form a much broader species complex (Swierts et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations